Kadar Kreatinin Serum pada Pasien Rawat Inap yang Didiagnosis Diabetes Melitus Tipe 2 - Tyas Pertiwi Armaningrum; Teguh Budiharjo (Jaringan Laboratorium Medis, 2022)
Uncontrolled Diabetes Mellitus will lead to long-term complications, namely decreased organ function, especially the kidneys, nerves, eyes, blood vessels and heart. Diabetic nephropathy is a complication that is often found in DM patients and attacks the kidneys. Serum creatinine examination is used to assess kidney function in patients with Type 2 Diabetes Mellitus. This purpose of research is to describe the description of serum creatinine levels in inpatients diagnosed with Type 2 Diabetes Mellitus at Dr. Kariadi Semarang. This study uses descriptive quantitative. The data comes from the medical records of inpatients diagnosed with Type 2 DM at Dr. RSUP. Kariadi Semarang who examined creatinine levels in the period January - April 2020 with the total sampling method. From this study, inpatients diagnosed with Type 2 DM at Dr. Kariadi Semarang were 79 respondents with male sex as many as 49 people (62%) and women 30 people (38%). In 79 respondesnts, there are 2 respondents (2.5%) had low creatinine levels, 7 respondents (8.9%) had normal creatinine levels, while 70 respondents (91.1%) had high creatinine levels. 43 male patients (88.6%) were included in the category of high creatinine levels. Based on age, it was dominated by the late elderly (55 – 65 years) as many as 32 people (40.5%) with the late elderly patients as many as 28 people (87.5%) having high creatinine levels. Conclusion: In 79 respondesnts (100%), there are 72 respondents (91.1%) who have abnormal creatinine levels and 7 respondents (8.9%) have normal creatinine levels.